Migrant Workers as Cultural Intermediaries - Madrah, Muna Yastuti; Suharko, Suharko (KOMUNITAS: International Journal of Indonesian Society and Culture, 2019)
This article aims at proposing an analysis formula on how the mechanism of cultural intermediaries done by Indonesian migrant worker student. The subject of this study were Indonesia migrant worker students in Korea undertaking higher education while under the contract as migrant workers. Various previous research on migrant workers mostly put them as "those who are powerless or unskilled." The emergence of these migrant worker students reflects that there is a change in values in viewing immaterial consumption by migrant workers. There is a kind of trendsetter (role model) that might influence them to enter the university as well as mediate new culture to other migrant workers. In this context, they are mediating the importance of having a higher education. Cultural intermediaries have an important role in creating a new social class. Many research reported, those involved in the work of cultural intermediaries include music critics, fashion directors, bloggers, stylists, advertisers, brand agents- refer to a certain social class. However, there has not been much research on intermediary work carried out by migrant workers. This study conveys a new perspective placing migrant workers as actors involved in mediating "cultural products" and consumption of "tastes" of consumers.